2016
DOI: 10.3233/cbm-160574
|View full text |Cite
|
Sign up to set email alerts
|

An insertion/deletion polymorphism in the interleukin-1A 3'untranslated region confers risk for gastric cancer

Abstract: These findings suggest that functional polymorphism rs3783553 in IL-1A could contribute to GC susceptibility, possibly or at least partially through affecting the transcriptional activity of IL-1A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…We selected the rs3783553 according to the following criteria: (1) rs3783553 located in the 3’-UTR of IL-1A , with a function of disrupting the binding site of miR-122 and miR-378 [ 16 , 29 ] ; (2) IL-1α is a critical mediator of inflammatory responses in IS; and (3) miR-122 may be used as a biomarker in IS, involving in the process of postischemic neuronal damage. [ 16 18 ] From each subject, 2 to 3 mL venous blood sample was collected.…”
Section: Methodsmentioning
confidence: 99%
“…We selected the rs3783553 according to the following criteria: (1) rs3783553 located in the 3’-UTR of IL-1A , with a function of disrupting the binding site of miR-122 and miR-378 [ 16 , 29 ] ; (2) IL-1α is a critical mediator of inflammatory responses in IS; and (3) miR-122 may be used as a biomarker in IS, involving in the process of postischemic neuronal damage. [ 16 18 ] From each subject, 2 to 3 mL venous blood sample was collected.…”
Section: Methodsmentioning
confidence: 99%
“…In term of rs3783553, it is a contention of a hundred schools of thought. It includes researches on multiple systems of cancer diseases, such as hepatocellular carcinoma, nasopharyngeal cancer, glioma, prostate cancer, gastric cancer, thyroid carcinoma, oral squamous cell carcinoma, cervical cancer, ovarian cancer, colorectal cancer, colorectal cancer, and endometrial cancer [37,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] . Analyzed by ethnicity, most of studies focus on Asians, yet researches direct to Caucasians are also quite a lot.…”
Section: Literature Searches and Characteristicsmentioning
confidence: 99%
“…Genome‐wide analysis has revealed that small insertion/deletions (INDELs) are the second most common type of genetic variants after single nucleotide polymorphisms (SNPs) in the human genome and they are likely to have a significant impact on human biology and diseases . Some studies have suggested that some INDELs are related to many cancers including gastric and hepatocellular carcinoma . In this regard, rs199971565 is an INDEL located in miR‐302c, which may affect its function and biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Some studies have suggested that some INDELs are related to many cancers including gastric and hepatocellular carcinoma. 20,21 In this regard, rs199971565 is an INDEL located in miR-302c, which may affect its function and biogenesis. To the best of our knowledge, no genetic association study has been conducted on this INDEL with any disease by now.…”
mentioning
confidence: 99%